The Illusive Quest for Structural Transformation in Africa: Will China Make a Difference?. (17th August 2018) - Geda, Alemayehu; Senbet, Lemma W; Simbanegavi, Witness
Abstract: Despite various attempts since independence and the growing economic engagement between China and Africa in the last two decades, structural transformation in Africa has remained elusive. In the last six decades, and unlike China and East Asian countries, African countries failed to successfully transform their economies and thus upgrade their industrial capabilities to move up the ladder of value addition. There is, however, renewed efforts by African countries to industrialise as one of the ways to structurally transform their economies. African countries should 'leverage their backwardness' to attract industries and technologies that are consistent with their comparative advantages (Lin, 2018 ). Indeed, there appears to be growing interest in Africa from the Chinese labour-intensive manufacturing, who see Africa as a low cost production region, especially given the rising labour costs in China. With clear strategic policy direction, African countries can take advantage of the imminent relocation of a substantial share of China's 85 million manufacturing jobs. This is not a foregone conclusion, since other regions are also trying to exploit this opportunity, and hence requiring African countries to solidify their competitive advantage for the imminent relocation. The studies, in this issue, while cautiously optimistic about the potential positive contribution of China for Africa's structural transformation, underscore that such success is conditional on African capability and informed strategic policy making and implementation in a pragmatic manner.